2016
DOI: 10.1136/bmjopen-2016-012185
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Diabetes Medication Choice Decision Aid in patients with type 2 diabetes in Greece: a cluster randomised trial

Abstract: ObjectiveTo assess the efficacy of the Diabetes Medication Choice Decision Aid among patients with type 2 diabetes in Greece.DesignOpen-label cluster randomised controlled trial.SettingPrimary and secondary care practices across Greece.Participants5 sites allocated to the decision aid (n=101 patients) and 4 sites to control (n=103 patients).InterventionClinicians and patients in the intervention arm used a decision aid, based on outcomes that both consider important when choosing among antihyperglycaemic medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(69 citation statements)
references
References 43 publications
0
68
0
1
Order By: Relevance
“…When synthesizing data for five trials, we did not detect any difference between use of PtDAs and usual care in terms of self-reported medication adherence (RR 1.06, 95% CI 0.96 to 1.17, I 2 = 38%) (Fig. Moreover, three studies used pharmacy records to measure adherence to medication prescription and reported results either as a dichotomous [22] or a continuous outcome [27,29], whereas one study assessed adherence to anti-hypertensive or statin therapy using both pharmacy records and self-reported uptake after 6 months [23]. Moreover, three studies used pharmacy records to measure adherence to medication prescription and reported results either as a dichotomous [22] or a continuous outcome [27,29], whereas one study assessed adherence to anti-hypertensive or statin therapy using both pharmacy records and self-reported uptake after 6 months [23].…”
Section: Medication Adherencementioning
confidence: 84%
See 4 more Smart Citations
“…When synthesizing data for five trials, we did not detect any difference between use of PtDAs and usual care in terms of self-reported medication adherence (RR 1.06, 95% CI 0.96 to 1.17, I 2 = 38%) (Fig. Moreover, three studies used pharmacy records to measure adherence to medication prescription and reported results either as a dichotomous [22] or a continuous outcome [27,29], whereas one study assessed adherence to anti-hypertensive or statin therapy using both pharmacy records and self-reported uptake after 6 months [23]. Moreover, three studies used pharmacy records to measure adherence to medication prescription and reported results either as a dichotomous [22] or a continuous outcome [27,29], whereas one study assessed adherence to anti-hypertensive or statin therapy using both pharmacy records and self-reported uptake after 6 months [23].…”
Section: Medication Adherencementioning
confidence: 84%
“…In one study, risk of bias assessment was based only on data presented in a conference abstract without contacting the corresponding authors [23]. Overall, eight studies were considered low risk [22,24,28,29,31,[34][35][36], four raised some concerns [23,30,33,37] and three studies were deemed at high risk of bias [25,27,38] due to concerns about the randomization process [25], high attrition rate [38] and inclusion of a participating practice after randomization [27].…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 3 more Smart Citations